COMPREHENSIVE ANALYSIS OF ORTHOPEDIC RESIDENT TRAINING PROGRAMS: EVALUATING CLINICAL ROTATIONS, SURGICAL SKILL DEVELOPMENT, AND POSTGRADUATE EDUCATION INITIATIVES. - ZAINALABIDIN ALI AL HUTAYLAH, ‏MOHAMMED NAJI AL YAMI-2, FAISAL NASSER HUSSIEN ALHUTAYLAH-5, ‏IBRAHIM ABDULLAH BIN YAHYA AL BAKRI-6, IBRAHIM SALEH HUSSAIN ALHUTAYLAH-7, MAJED SALEH HUSSAIN AL HOTELAH-8, HADI MOHAMMED WABRAN ALYAMI -9, ABDULLAH HASSAN BIN S (Chelonian Research Foundation, 2022)
Engagement in residency programs for orthopedic surgeon training promotes the next generation of orthopedists to provide quality patient care. Such multidimensional analysis deals with multiple aspects of orthopedic residents' training programs, such as clinical rotations, surgical skill development, and rotatory programs for graduates. This research aims to find the strengths, weaknesses, and recommendations with the help of careful literature and empirical analysis to improve training programs for orthopedic residents. The central idea of the findings is that practical clinical matters, surgical training in the operating room, and all-time educational experiences are the most critical components that should be included in the education of orthopedic residents. Keywords: orthopedic resident training, surgical exercises, communicational skills, postgraduate education, and more.